2003
DOI: 10.1037/0022-0663.95.4.707
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Comprehension of Main Ideas in Narratives: Evidence From the Selection of Titles.

Abstract: The authors investigated readers' ability to identify main ideas in narrative texts and the development of this ability. In particular, the authors explored students' sensitivity to the goal structure of narratives. Third-, 6th-, 9th-, and 11th-grade students read narratives in which goal statements were systematically varied on 2 structural dimensions: position in the text's hierarchical structure and number of connections to other statements. As a measure of main idea comprehension, students selected titles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 44 publications
1
33
0
4
Order By: Relevance
“…In addition, the reader has to analyse the text before evaluating it (Kaplan, 2013). Thus, our results are in accordance with earlier studies which have shown that students at this age are better in tasks which require much lower-level cognitive skills (Kaplan, 2013;Uibu, & Mannamaa, 2014;Van den Broek et al, 2003;Veeravagu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the reader has to analyse the text before evaluating it (Kaplan, 2013). Thus, our results are in accordance with earlier studies which have shown that students at this age are better in tasks which require much lower-level cognitive skills (Kaplan, 2013;Uibu, & Mannamaa, 2014;Van den Broek et al, 2003;Veeravagu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Problems occur when texts have to be analyzed, evaluated and integrated with student's prior knowledge (Pandis, 2008;Sinka, 2008). By the age of 15 students should have the cognitive skills to analyse, evaluate and integrate texts (Van den Broek, Lunch, Naslund, Levers-Landis & Verduin, 2003). That is why it is important to study the students' text comprehension at the age of 10-12.…”
Section: Changes In Text Comprehension Skills At the Basic School Levelmentioning
confidence: 99%
“…He argued that part of young children's difficulty in extracting the gist of televised stories is that they tend to forget the main character's superordinate goal, even though this goal typically serves as the narrative glue that binds the events of the story together (Van den Broek, 1997;van den Broek, Lynch, Naslund, Ievers-Landis, & Verduin, 2003). Not surprisingly then, Mares (2006) found that when 6-to 8-year-old children were asked to generate the moral lessons of the Disney animated film, The Sword in the Stone, very few did so correctly.…”
Section: More General Difficulties Extracting the Gist Of Televised Smentioning
confidence: 99%
“…Goal structure understanding also increases understanding of main ideas (van den Broek et al, 2003). Few studies have investigated the impact of variations in goal structures.…”
Section: Narrative Comprehension: the Constructionist Paradigmmentioning
confidence: 99%